A non-indigenous ethnomusicologist in «listen» with the Emberá Chamí - Molano Zuluaga, Juan Carlos (2020)
This article is a proposal from a framework of theoretical-methodological nature based on the intercultural experience of hearing that the Colombian anthropologist Luis Guillermo Vasco had in the 70’s with the shamanic practices of the Emberá Chamí. This guideline, gives an insight into determining some questionings with respect to the fieldwork undertaken by this anthropologist concerning the listening; as an ear that cared and translated certain hearing significances to certain cultural settings. Meanwhile, these ethnomusicological interpretations are given from these guidelines and confronted by my insertion and participation in the fieldwork in an event of «toma» or intake of ayahuasca in the Emberá Chamíindigenous reservation from San Lorenzo.